Homologous and heterologous prime boost vaccinations with distinct variants of Plasmodium vivax circumsporozoite protein (CSP) protects mice against transgenic PB/PV sporozoite challenge - Freitas, E; Camargo, T; Gimenez, A; Lima, L; Caramico, K; Francoso, K; Bruna-Romero, O; Ertl, H; Nussenzweig, R; Nussenzweig, V; Rodrigues, M; Reyes-Sandoval, A; et al. (American Society of Tropical Medicine and Hygiene, 2017)
Vaccine development against Plasmodium vivax malaria lags behind that for Plasmodium falciparum. To narrow this gap, we administered recombinant antigens based on P. vivax circumsporozoite protein (CSP) to mice.